Biosimulation in biomedical research, health care and drug development - Sosnovtseva, Olga; Rostami-Hodjegan, Amin; Mosekilde, Erik (Springer Vienna, 2012)
Biosimulation is an approach to biomedical research and the treatment of patients in which computer modeling goes hand in hand with experimental and clinical work. Constructed models are used to interpret experimental results and to accumulate information from experiment to experiment. The book explains the concepts used in the modeling of biological phenomena and goes on to present a series of well-documented models of the regulation of various cellular and physiological processes, emphasizing particularly the role of self-sustained biological activity. The way how the use of computer models allows optimization of the treatment of various diseases for individual patients is discussed and models of interacting nerve cells that can be used to design new treatments for patients with Parkinson's disease are explained. Furthermore this volume provides a discussion of the use of models in the pharmaceutical industry, and presents the view of the regulatory agencies on the topic.